Nilai Slump Ideal untuk Perencanaan Campuran Beton Mutu 50 MPa - Iskandar, Iskandar; Tjitradji, Darmansyah; Eliatun, Eliatun (Department of Civil Engineering, Diponegoro University, 2005)
Recently, the need of the high strength concrete is increased, because of the rapid technology development in the concrete technology area. In the performing of the high strength concrete is rather difficult on the mixing, pouring, and vibrating, because, the raw concrete mix is very viscous. The aim of this research is to find out the ideal slump value of the high strength concrete mix which is used the local aggregate with superplasticizer and silica fume, therefore it can be performed the good workability of the fresh concrete and design strength of the concrete (f’c = 50 MPa) could be reached. The experiment was conducted by compressive strength testing on one hundred twenty cylinder specimens with the slump value of 0-10 mm, 10-30 mm, 30-60 mm and 60-180 mm. As the result of the test is obtained the idealized design slump value is 30–60 mm. Keywords: high strength concrete, local aggregate, slumpPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3903[How to cite: Iskandar, Tjitradi, D. dan Eliatun, 2005, Nilai Slump Ideal untuk Perencanaan Campuran Beton Mutu 50 MPa, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 1-10]